Analizyng Ridha As a Mediator Within the BDI Model: A Study on Middle-Class Preferences for Muslim-Friendly Cafes - Amir, Nur Buana; Razak, Syaparuddin; Jumarni, Jumarni (Iqtishodia: Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the impact of Muslim-friendly cafes on customer satisfaction using the BDI (Belief, Desire, Intention) model framework. The main focus is on how the concept of ridha (spiritual satisfaction) can be measured by customers visiting these cafes. A survey was conducted with 161 middle-class Muslim respondents in South Sulawesi using a Likert scale, and data were analyzed through Structural Equation Modeling (SEM) with SmartPLS 4. Results show that belief, desire, and intention significantly influence the decision to visit. Key factors enhancing satisfaction include halal product quality, good service, and a comfortable Islamic atmosphere. Worship facilities, like prayer rooms, also add value. Muslim-friendly cafes attract both Muslim and non-Muslim customers interested in quality. Religious and cultural factors play a crucial role in shaping Muslim consumer behavior. Marketing strategies incorporating BDI elements and spiritual satisfaction can boost visits and customer loyalty.